Efektivitas Terapi Relaksasi Nafas Dalam untuk Menurunkan Nyeri Akut pada Pasien Fraktur di RSUD Hajjah Andi Depu - Ambohamsah , Idawati; Nur, Hamdan; Fauziah, Dian (Mando Care Jurnal, 2024)
A fracture or fracture is a disruption of the continuity of both total, partial bone tissue that can affect the long bone, joints of muscle tissue and blood vessels causing injury to the movement of the limb. Each individual will adapt to the changes that occur. At RSUD Hajja Andi Depu, the number of fractural patients by 2022 reached 157 people. The study aims to investigate the effectiveness of giving deep breath relaxation techniques to patients with fractures with moderate pain. The research project uses one group pre-post test design with a total sample of 22 respondents with purposive sampling techniques. Pain analysis is measured using the Numerc Rating scale. The study used univariate and bivariate analysis. From the results of the study showed the average prior to the inhalation technique is 6.27 and the average result after the given inhaling technique is 3.54. The bivariate result obtained p-value =0,001 <0,05 so it can be concluded that the action of breathing relaxation technique in effective in reducing the intensity of pain in patients fractures.